Antibacterial poly(lactic acid) (PLA) films grafted with electrospun PLA/allyl isothiocyanate fibers for food packaging. Issue 2 (11th June 2015) - Kara, Hasan H.; Xiao, Fugang; Sarker, Majher; Jin, Tony Z.; Sousa, Ana M. M.; Liu, Cheng‐Kung; Tomasula, Peggy M.; Liu, LinShu; Lagarón, José M.; López‐Rubio, Amparo; Fabra, María José
ABSTRACT Poly(lactic acid) (PLA) fibers of submicron sizes encapsulating allyl isothiocyanate (AITC) (PfA) were made and electrospun onto the surfaces of PLA films. SEM examination confirmed the fusion of the two phases to form a bilayered fiber‐grafted film after the film underwent air blowing and water washing to remove the nongrafted fibers. The fiber‐grafted PLA films (PfA‐g‐film) retain the mechanical properties of PLA. The release of AITC from the fibers was temperature dependent. At temperatures lower than 4°C, the incorporated AITC remained within the fibers without losing activity; at room temperature, AITC released in a sustained manner over weeks. The release of AITC was also dependent on its initial concentration in the PLA electrospinning solution; samples with more AITC incorporated showed a higher release rate. PfA‐g‐films significantly inhibited the growth of Listeria innocua and Escherichia coli k12 when tested on package foods. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 42475.